Unethical behaviour in Human Resource Management practices in South Africa: Views of Human Resource practitioners - Barney J. Earsmus (Management : Journal of Contemporary Management Issues, 2018)
The study on which this article reports, examined the relationship between the susceptibility of unethical behaviour in human resource (HR) practices (dependent variable) and three independent variables, namely the role of the HR function in institutionalising good business ethics, factors influencing the personal ethical behaviour of HR practitioners, and the commitment to ethical business conduct, exhibited by certain individuals and groups within organisations. A descriptive study was undertaken using an online questionnaire, and 304 HR practitioners in South Africa participated. The results indicated that employee selection, performance management and appraisal, recruitment and advertising were the areas most susceptible to unethical HR practices. The least susceptible HR areas were affirmative action, employment equity plans, employee orientation, employee socialisation, and psychometric testing. The results also showed statistically significant relationships among the independent variables and the dependent variable. Amongst others findings, a statistically significant positive relationship existed between susceptible unethical HR practices when HR practitioners are solely responsible for resolving ethical dilemmas, and a negative relationship when HR is not directly involved with resolving ethical dilemmas. The HR function has an important role and contributes to institutionalising business ethics in organisations.